2018
DOI: 10.1177/1179069518779829
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Functional Basis of Dopamine Receptors and Their Role in Neurogenesis: Possible Implication for Parkinson’s disease

Abstract: Dopamine controls various physiological functions in the brain and periphery by acting on its receptors D1, D2, D3, D4, and D5. Dopamine receptors are G protein–coupled receptors involved in the regulation of motor activity and several neurological disorders such as schizophrenia, bipolar disorder, Parkinson’s disease (PD), Alzheimer’s disease, and attention-deficit/hyperactivity disorder. Reduction in dopamine content in the nigrostriatal pathway is associated with the development of PD, along with the degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(141 citation statements)
references
References 107 publications
6
130
0
5
Order By: Relevance
“…D2-like receptors are mainly expressed in the striatum, external globus pallidus, nucleus accumbens, amygdala, cerebral cortex, hippocampus, and pituitary gland. These receptors are involved in movement control, impulses, and cognition (Mishra et al, 2018). Previous studies have suggested that dopaminergic projections originating from the SN pars compacta activate the D2 and D4 receptors in the TRN, thereby suppressing GABA signaling (Behrendt, 2006).…”
Section: Dopaminergic Systemmentioning
confidence: 99%
“…D2-like receptors are mainly expressed in the striatum, external globus pallidus, nucleus accumbens, amygdala, cerebral cortex, hippocampus, and pituitary gland. These receptors are involved in movement control, impulses, and cognition (Mishra et al, 2018). Previous studies have suggested that dopaminergic projections originating from the SN pars compacta activate the D2 and D4 receptors in the TRN, thereby suppressing GABA signaling (Behrendt, 2006).…”
Section: Dopaminergic Systemmentioning
confidence: 99%
“…Гены рецепторов дофамина. Физиологический эффект дофамина опосредован через пять классов дофаминовых рецепторов (D1-D5), сопряженных с G-белком (G-proteincoupled receptors, GPCRs) [41]. Высокий уровень экспрессии D1-рецепторов обнаружен в нигростриарной, мезолимбической и мезокортикальной областях.…”
Section: ген моноаминооксидазы типа в (мао-в)unclassified
“…Ген дофаминового D2-рецептора (DRD2) локализуется на 11-й хромосоме (11q23.1), имеет 6 интронов в кодирующем регионе. Агонистом D2-рецепторов являются бромокриптин, перголид, каберголин и ропинирол [41]. В гене DRD2 описан микросателлитный, или состоящий из коротких тандемных повторов (short tandem repeat, STR), полиморфизм (CAn-STR).…”
Section: ген моноаминооксидазы типа в (мао-в)unclassified
“…Those are D 1 and D 2 dopamine receptors [ 29 ], dopamine transporter (DAT) [ 30 ], GluNs [ 31 , 32 ], neurotrophine receptor trkB [ 33 ], IP 3 R3 within the MAM region [ 34 ], main ER chaperone BiP [ 34 , 35 ], ER stress sensor IRE1 [ 36 ], and nucleus membrane protein emerin [ 37 ]. These interactions modulate the activity of client proteins [ 29 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , 39 , 40 ] and may contribute to the protective effect in dopaminergic neurons of nigrostriatal tracts [ 10 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%